2019
DOI: 10.1017/s0950268819000670
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing for improved understanding of Mycobacterium tuberculosis transmission in a remote circumpolar region

Abstract: Few studies have used genomic epidemiology to understand tuberculosis (TB) transmission in rural and remote settings – regions often unique in history, geography and demographics. To improve our understanding of TB transmission dynamics in Yukon Territory (YT), a circumpolar Canadian territory, we conducted a retrospective analysis in which we combined epidemiological data collected through routine contact investigations with clinical and laboratory results. Mycobacterium tuberculosis isolates from all culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In California, WGS allowed public health workers to refute more than half of suspected outbreaks initially identified by conventional genotyping, saving time and resources (personal communication, Tambi Shaw, California Department of Public Health). Early experience in U.K., 5 Canadian, 31,32 and Dutch 33 tuberculosis programs has also confirmed that WGS supports more effective investigations by more accurately defining outbreaks 5,31,33 , providing insights into transmission dynamics, 34 and sometimes suggesting the presence of previously unidentified cases or possible "super-spreaders" that should be prioritized for isolation and treatment. 5,31 WGS may also indicate whether recurrent cases are due to reactivation or reinfection, information useful in evaluating program effectiveness.…”
Section: Tuberculosismentioning
confidence: 81%
“…In California, WGS allowed public health workers to refute more than half of suspected outbreaks initially identified by conventional genotyping, saving time and resources (personal communication, Tambi Shaw, California Department of Public Health). Early experience in U.K., 5 Canadian, 31,32 and Dutch 33 tuberculosis programs has also confirmed that WGS supports more effective investigations by more accurately defining outbreaks 5,31,33 , providing insights into transmission dynamics, 34 and sometimes suggesting the presence of previously unidentified cases or possible "super-spreaders" that should be prioritized for isolation and treatment. 5,31 WGS may also indicate whether recurrent cases are due to reactivation or reinfection, information useful in evaluating program effectiveness.…”
Section: Tuberculosismentioning
confidence: 81%
“…The fourth discordant case had a MIRU-VNTR pattern common to both YT and BC, and while WGS placed this isolate with a genomically distinct YT sub-cluster within this group (see Fig. 3: WClust-1 in our previous work [18]), the field team classified the individual with this isolate as having acquired TB within BC based on epidemiological information.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…When we compared source case assignments during the in-person consensus meeting, the discussion revealed that the team using field-based data struggled with the complex social network of this cluster – many connections between individuals, while the team using WGS data were challenged by the minimal genomic diversity between YT isolates (0–4 SNVs). The presence of a minority variant in one WClust-1 case [18] divided the cluster into two genomically linked sub-clusters, facilitating source identification at the consensus meeting. While there was no strong agreement between the two team's source case assignments, the field-based methods did accurately link individuals to the correct WClust-1 genomic sub-cluster for 11 of 13 persons (85%) with only one individual linked to the incorrect genomic sub-cluster, and a second individual thought to have acquired their infection in BC due to an absence of clear epidemiological connections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations